Market Segmentation and Competition in Health Insurance - Dickstein, Michael J.; Ho, Kate; Mark, Nathaniel (Journal of Political Economy, 2024)
In the United States, households obtain health insurance through distinct market segments. To explore the economics of this segmentation, we consider the effects of pooling coverage provided through small employers and through individual marketplaces. We model households’ demand for insurance and health care along with insurers’ price setting to predict equilibrium choices and premiums. Applying our model to data from Oregon, we find that pooling can mitigate adverse selection in the individual market and benefit small group households without raising taxpayer costs. Our estimates provide insight into the effects of new regulations that allow employers to shift coverage to individual marketplaces.